Overview of the State of Child Nutritional Status Based on Accreditation in TK Sejahtera 4 Tasikmalaya City - Wilda Salmah; Heri Yusuf Muslihin; Aini Loita (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Pre-school children experience various nutritional problems, including malnutrition and excess nutrition where the number is increasing every year. This is also supported by the Monthly Report (LB) from the Tasikmalaya City Health Office, reporting that the number of toddlers suffering from malnutrition in 2021 was found to be 0.82% in Tasikmalaya City. An absolute prerequisite for development in all fields is the quality of human resources (HR). Several important factors influence the quality of human resources, especially factors related to intelligence, productivity and creativity, including nutritional status. PAUD school accreditation provides very important participation in improving the nutritional status of pre-school-age children through comprehensive education, nutrition services, child health and early detection of child growth and development. This research was conducted with the aim of seeing how the nutritional status of children is described based on accreditation at PAUD school institutions. Researchers used a qualitative approach with data collection techniques through observation and interviews. This research resulted in that there is an effect of the accreditation of an PAUD institution on the nutritional status of children in Kindergarten Sejahtera 4.